NURSE CARE IN RESPIRATORY ORGAN DISEASES - Rakhmanova Mashkhura; Latipova Feruzakhon (Journal Park Publishing, 2023)
It is known that the respiratory system includes the nasal passages, hiccups, trachea, bronchi, lungs. The lungs will be surrounded on the outside by a thin elastic connective tissue - the pleura veil. The right lung is composed of three: upper, lower, middle; and the left lung is composed of two: upper and lower. The lungs are located in the chest. Between the right and left lungs are the stuttering, esophagus, blood vessels, the aisimon gland, nerve fibers, lymphatic vessels and nodes, and the heart. The lower surface of the lungs touches the diaphragm, a barrier between the chest and the abdomen. The article provides information on nurse care in respiratory organ diseases.
Keywords: disease, respiratory organs, medical prevention, disease treatment, medical culture.